(untitled) (Third Sector Social Economic Review, 2019)
When a financial institution is an Interest-free Financial Institution (IFI) operating under Islamic rules, Islamic rules are added to the elements that need to be audited. Considering the Islamic finance sector, which is expected to reach a total value of 6.5 trillion USD by 2020, the audit of a company operating in this sector is of great importance. The audit provides assurance that the business activities are in compliance with the legislation and that the financial reports reflect the truth fairly and honestly, whereas it does not guarantee that the activities are carried out in accordance with Islamic rules. Therefore, the relevance of the activities carried out by the IFIs to Islam is of great importance for those who want to conduct commercial transactions with IFIs or who want to invest in these institutions. In order to shed light on the subject, the IFI audit is handled in terms of both internal audit and independent audit.